EXAMINING HOW HARMONIOUS WORK PASSION MEDIATED WELL-BEING ORIENTED MANAGEMENT AND INNOVATIVE WORK BEHAVIOR - Pramusiwi, Aloysia Desy; Putra, Tegar Satya; Putranta, Martinus Parnawa (Stability: Journal of Management and Business, 2024)
Innovation is essential for organizational success to be adaptive to this dynamic business situation. Organizational innovation is highly dependent on employees' innovative work behavior regarding the level of creativity and proactive behavior. This study aims to determine the effect of well-being-oriented management on innovative work behavior through harmonious work passion as mediation. This study uses social exchange theory and the job-demand resources model to be able to describe how to increase the level of employee creativity. This research method is quantitative by distributing questionnaires using a purposive sampling method with 150 respondents. SEM-PLS is used to analyze data in this study. The results of this study indicate that well-being oriented management has a positive effect on harmonious work passion, and harmonious work passion has a positive effect on innovative work behavior. In addition, harmonious work passion mediates the relationship between well-being oriented management and innovative work behavior. Thus, organizations need to maintain employee well-being through well-being oriented management because it can impact employee behavior at work.